Cytotoxic cardenolides from the latex of Calotropis procera. Issue 20 (15th October 2015) - Mohamed, Nadia H.; Liu, Miaomiao; Abdel-Mageed, Wael M.; Alwahibi, Lamya H.; Dai, Huanqin; Ismail, Mady Ahmed; Badr, Gamal; Quinn, Ronald J.; Liu, Xueting; Zhang, Lixin; Shoreit, Ahmed A.M.
Graphical abstract: Abstract: Three new cardenolides (3, 9 and10 ), along with eight known ones, were isolated from the latex of Calotropis procera . The structural determination was accomplished by the 1D- and 2D-NMR spectra as well as HRESIMS analysis. The growth inhibitory activity of the latex and its sub-fractions as well as isolated compounds was evaluated against human A549 and Hela cell lines. The results exhibited that latex had strong growth inhibitory activity with IC50 s of (3.37 μM, A-549) and (6.45 μM, Hela). Among the four extracts (hexane, chloroform, ethyl acetate and aqueous), chloroform extract displayed the highest potential cytotoxic activity, with IC50 s of (0.985 μM, A-549) and (1.471 μM, Hela). All the isolated compounds displayed various degrees of cytotoxic activity and the highest activity was observed by calactin (1 ) with IC50 s values of (0.036 μM, A-549) and (0.083 μM, Hela). None of these isolated compounds exhibited good antimicrobial activity evaluated by determination of their MICs using the broth microdilution method against various infectious pathogens. The structure–activity relationships for cytotoxic activity were also discussed.